OP-1 Compared with Iliac Crest Autograft in Instrumented Posterolateral Fusion: A Randomized, Multicenter Non-Inferiority Trial. (16th March 2016) - Delawi, Diyar; Jacobs, Wilco; van Susante, Job L.C.; Rillardon, Ludovic; Prestamburgo, Domenico; Specchia, Nicola; Gay, Emmanuel; Verschoor, Nico; Garcia-Fernandez, Carlos; Guerado, Enrique; Quarles van Ufford, Henriette; Kruyt, Moyo C.; et al.
Abstract : Background: Spinal fusion with the use of autograft is a commonly performed procedure. However, harvesting of bone from the iliac crest is associated with complications. Bone morphogenetic proteins (BMPs) are extensively used as alternatives, often without sufficient evidence of safety and efficacy. The purpose of this study was to investigate non-inferiority of osteogenic protein-1 (OP-1, also known as BMP-7) in comparison with iliac crest bone graft in posterolateral fusions. Methods: This study was a randomized, controlled multicenter trial. Patients who underwent a single-level instrumented posterolateral fusion of the lumbar spine for degenerative or isthmic spondylolisthesis with symptoms of neurological compression were randomized to receive OP-1 combined with local bone (OP-1 group) or autologous bone graft from the iliac crest combined with local bone (autograft group). The primary outcome was overall success, defined as a combination of clinical success and evidence of fusion on computed tomography (CT) scans, at one year postoperatively. Results: One hundred and nineteen patients were included in the study, and analysis of the overall outcome was performed for 113. Non-inferiority of OP-1 compared with iliac crest autograft was not found at one year, with a success rate of 40% in the OP-1 group versus 54% in the autograft group (risk difference = −13.3%, 90% confidence interval [CI] = −28.6% to +2.10%). This was due to the lower rate of fusion (the primary aim of OP-1 application) seen on the CT scans in the OP-1 group (54% versus 74% in the autograft group, p = 0.03). There were no adverse events that could be directly related to the use of OP-1. Conclusions: OP-1 with a collagen carrier was not as effective as autologous iliac crest bone for achieving fusion and cannot be recommended in instrumented posterolateral lumbar fusion procedures. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.